Microwave irradiation-assisted transesterification of ternary oil mixture of waste cooking oil Jatropha curcas Palm oil: Optimization and characterization - Yusoff M.N.A.M.; Zulkifli N.W.M.; Sukiman N.L.; Kalam M.A.; Masjuki H.H.; Syahir A.Z.; Awang M.S.N.; Mujtaba M.A.; Milano J.; Shamsuddin A.H. (Elsevier B.V., 2023)
Catalysts; Feedstocks; Irradiation; Methanol; Microwave irradiation; Mixtures; Molar ratio; Palm oil; Potassium hydroxide; Surface properties; Transesterification; Biodiesel feedstock; Irradiation methods; Jatropha curcas; Microwave irradiation method; Microwave- irradiations; Oil mixtures; Optimisations; Response-surface methodology; Transesterifications; Waste cooking oil; Biodiesel